2015
DOI: 10.1111/jpn.12303
|View full text |Cite
|
Sign up to set email alerts
|

Performance of growing cattle on poor‐quality rangelands supplemented with farm‐formulated protein supplements in Zimbabwe

Abstract: Farmers use different non-conventional protein supplements and different feeding strategies to aid their animals survive the dry season in Zimbabwe. The strategies can be giving supplements once a week or once every other day up to very little supplement daily. Supplements are either legume crop residues or forage legumes. However, the efficacy of the use of non-conventional protein supplements in promoting growth and at the same time lowering the age at first calving is little understood. The study tested whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Partial or complete substitution of feed ingredients with forages or poultry litter as protein sources enabled farmers to source feed locally, utilise what is available at the farm, whilst getting more or less the same animal perfomance as with commercial feed. Several studies have also concluded with recommending use of alternative protein sources to reduce feed and associated costs, thereby increasing overall profitability (Jokthan et al 2013;Mhaka 2014;Gusha et al 2015b). Fluctuations in the pricing of beef in Zimbabwe generally follow seasonal availability of beef quality and quantity.…”
Section: Economic Analysismentioning
confidence: 99%
“…Partial or complete substitution of feed ingredients with forages or poultry litter as protein sources enabled farmers to source feed locally, utilise what is available at the farm, whilst getting more or less the same animal perfomance as with commercial feed. Several studies have also concluded with recommending use of alternative protein sources to reduce feed and associated costs, thereby increasing overall profitability (Jokthan et al 2013;Mhaka 2014;Gusha et al 2015b). Fluctuations in the pricing of beef in Zimbabwe generally follow seasonal availability of beef quality and quantity.…”
Section: Economic Analysismentioning
confidence: 99%